Injury prevention attitudes and awareness in New Zealand. Issue 1 (1st March 2003) - Hooper, R; Coggan, C A; Adams, B
Abstract : Objectives: This study was designed to obtain New Zealand data on beliefs related to a broad spectrum of injuries and their prevention. Methods: A cross sectional phone survey was conducted of approximately 400 randomly selected households from each of 13 territorial local authorities across New Zealand, giving a total of 5282. Respondents were asked questions on awareness and attitudes to injury prevention, ownership and use of safety equipment, safety behaviours, and incidence of self reported injury. Results: 84% agreed with the statement that "Most injuries are preventable" and 91% rated their homes as "very safe" or "reasonably safe". A high proportion of homes had smoke alarms (81%) and first aid kits (81%), and more than half (56%) had turned down the temperature of their hot water to 55°C or lower. However, less than half of the respondents said that they practised the other safety behaviours. Significant associations were found between the practise of safety behaviours and respondents' home safety ratings. There was a significant association between home safety ratings and the incidence of injury occurring in all settings (p<0.0001), however there was no discernable association between home safety ratings and injury occurring in the home. Conclusions: Although this survey found that most respondents believed that injuries are preventable and considered their homes to be safe, the public need to be further encouraged to adopt common safety practices and behaviours in the home.